2009
DOI: 10.3892/ijo_00000352
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of selected microRNAs in melanoma: Antiproliferative and proapoptotic activity of miRNA-155

Abstract: Abstract. Altered expression of microRNAs (miRNAs) has been detected in cancer, suggesting that these small non-coding RNAs can act as oncogenes or tumor suppressor genes. In the present study, we investigated the expression of miRNA-17-5p, miRNA-18a, miRNA-20a, miRNA-92a, miRNA-146a, miRNA-146b and miRNA-155 by real-time quantitative RT-PCR in a panel of melanocyte cultures and melanoma cell lines and explored the possible role of miRNA-155 in melanoma cell proliferation and survival. The analyzed miRNAs were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…miR-155 promotes the degradation of the master gene involved in pigmentation and reduces the expression levels of TYRP1 Due to its role in several cancers, miR-155 is considered by the miRNA community as an oncomir, an miRNA involved in oncogenesis (Di Leva et al, 2014;Volinia et al, 2006). However, in melanoma, miR-155 likely acts as a tumor suppressor (Levati et al, 2009;Segura et al, 2010). The overexpression of synthetic miR-155 reduces the proliferation and viability of melanoma cells in culture (Gilot et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…miR-155 promotes the degradation of the master gene involved in pigmentation and reduces the expression levels of TYRP1 Due to its role in several cancers, miR-155 is considered by the miRNA community as an oncomir, an miRNA involved in oncogenesis (Di Leva et al, 2014;Volinia et al, 2006). However, in melanoma, miR-155 likely acts as a tumor suppressor (Levati et al, 2009;Segura et al, 2010). The overexpression of synthetic miR-155 reduces the proliferation and viability of melanoma cells in culture (Gilot et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of let-7a on expression of integrin beta 3 has been verified in another study (86). In addition, functional studies have shown the role of miR-155 in the suppression of proliferation of a number of melanoma cell lines and induction of apoptosis in these cells (16). Table 2 lists the down-regulated miRNAs in melanoma.…”
Section: Dysregulated Mirnas In Melanomamentioning
confidence: 76%
“…Two other miRNAs including miR-489 and miR-527 had the opposite pattern of expression (15). Levati et al have demonstrated up-regulation of miR-17-5p, miR-18a, miR-20a, and miR-92a while down-regulation of miR-146a, miR-146b and miR-155 in most of assessed melanoma cell lines compared with melanocytes (16).…”
Section: Dysregulated Mirnas In Melanomamentioning
confidence: 99%
“…It was found that expression of the receptor tyrosine kinase c-KIT decreased with melanoma progression [ 31 ], and that miR-221/222 expression increased with tumor progression and was inversely correlated with c-KIT expression [ 32 ]. Looking at the current results, we can also now include oncogenes determining the development of melanoma such as miR-21, miR-155, miR-182 and miR-214 [ 33 , 34 , 35 ].…”
Section: Biological Characteristics Of Micrornamentioning
confidence: 99%